Becoming Invisible - Ian Whittlesea (London; The Everyday Press, 2017)
Becoming Invisible wa produced in an edition of seven copies as part of an exhibition of the same name at Marlborough Contemporary, London in March 2013 and then as an edition of 1000 copies in London 2014. This edition produced in 2017.
English
Keywords: N4390-5098 Exhibitions